Beauty Beyond Products: Exploring the Drivers of Customer Satisfaction in Malaysia’s Leading Health and Beauty Retailer - Yong Yu Lee; Kun Peng Xia; Shi Ying Lee; Che Ying Lee; Huey Shan Lee; Wei Yin Lee; Yan Lin Lee; Varun Kumaran B; Anees Janee Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Drawing on service-dominant logic and the framework of stimulus-organism-response, our study investigates the mechanisms through which service attributes influence customer satisfaction in health and beauty retail. Analysis of survey data from 99 Watsons Malaysia customers reveals that staff behavior directly influences both perceived service quality and customer satisfaction, while service accessibility shapes satisfaction primarily through customer emotional responses and perceived service quality. The findings demonstrate the distinct pathways through which different service attributes contribute to satisfaction outcomes, with both cognitive and emotional responses playing crucial mediating roles. This study advances service management theory by illuminating the complex mechanisms underlying customer satisfaction formation and provides practical guidance for retail managers in designing effective service improvement initiatives. The results highlight the importance of considering both direct and indirect pathways when developing service enhancement strategies in health and beauty retail contexts.